Cover Image, Volume 6, Issue 5. (September 2016) - Santoro, Fabrizio; Jacquemin, Denis
Abstract : The front cover image, by Fabrizio Santoro and Denis M Jacquemin, is based on the Advanced Review Going beyond the vertical approximation with time‐dependent density functional theory, DOI:10.1002/wcms.1260 . Abstract : The front cover image, by Denis M Jacquemin and Fabrizio Santoro, is based on the Advanced Review Going beyond the vertical approximation with time‐dependent density functional theory, DOI:10.1002/wcms.1260 .